Biopsychosocial needs and perceptions on senior day care of the functional elderly in the Village of Dayap in Calauan, Laguna, Philippines - Torres, Renato V. (Journal of Human Ecology, 2011)
The Senior Day Care is necessarily satisfy the biopsychosocial need of the functional elderly. The study aims to determine the unmet biopsychosocial needs and perceptions on senior day care of 100 functional elderly, aged 60 years and above, in the village of Dayap in Calauan, Laguna.